2007
DOI: 10.3758/cabn.7.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of emotional intelligence in adolescent children

Abstract: The somatic marker hypothesis posits a key role for the ventromedial prefrontal cortex, amygdala, and insula in the ability to utilize emotions to guide decision making and behavior. However, the relationship between activity in these brain regions and emotional intelligence (EQ) during adolescence, a time of particular importance for emotional and social development, has not been studied. Using functional magnetic resonance imaging (f MRI), we correlated scores from the Bar-On Emotional Quotient Inventory, Yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 102 publications
(102 reference statements)
6
38
1
2
Order By: Relevance
“…These regions are rather (though, not completely) distinct from the regions involved in social cognition such as theory of mind, as described above. Brain activities during the perception of fearful faces were negatively correlated with EI in the somatic marker circuitry [Killgore et al, 2007]. Furthermore, previous lesion studies reported that lesions in the somatic marker circuitry [Bar-On et al, 2003] or the key node of the somatic marker circuitry, the VMPFC [Krueger et al, 2009] result in low emotional intelligence.…”
Section: Introductionmentioning
confidence: 83%
“…These regions are rather (though, not completely) distinct from the regions involved in social cognition such as theory of mind, as described above. Brain activities during the perception of fearful faces were negatively correlated with EI in the somatic marker circuitry [Killgore et al, 2007]. Furthermore, previous lesion studies reported that lesions in the somatic marker circuitry [Bar-On et al, 2003] or the key node of the somatic marker circuitry, the VMPFC [Krueger et al, 2009] result in low emotional intelligence.…”
Section: Introductionmentioning
confidence: 83%
“…Functional MRI studies have demonstrated that greater EI may be associated with reduced responsiveness of the amygdala, insula, and vmPFC among children and adolescents when viewing facial expressions of fear, suggesting greater neural efficiency of select affect processing systems in those with higher EI (i.e. requiring less neural effort during emotional processing) [9]. A recent study in adults has suggested that higher EI is associated with greater activation of the vmPFC and the rostral anterior cingulate cortex in response to dynamic facial expressions that changed in terms of perceived trustworthiness [10].…”
Section: Introductionmentioning
confidence: 98%
“…ERPs and fMRI have been used to study a wide variety of psychological processes in children: including cognitive (Bitan et al, 2007;Weber-Fox, Hart, & Spruill, 2006), affective (Killgore & Yurgelun, 2007;Pérez-Edgar & Fox, 2003), sensorimotor (Johannes et al, 2001;Mall et al, 2005), attentional (Perez-Edgar et al, 2007;Steven & Friedman, 1995) and executive processes (Dimoska, Johnstone, & Barry, 2006;Durston, Thomas, Wordon, Yang, & Casey, 2002). In particular, topics subsumed by executive control have been the target of a great deal of research, including attention orienting (Perchet & GarciaLarrea, 2005), distractability (Wetzel & Schroger, 2007), inhibition of a motor response (Ciesielski, Harris, & Cofer, 2004), response-and error-monitoring (Hogan, Vargha-Khadem, Kirkham, & Baldeweg, 2005), and conflict/interference detection (Rueda, Posner, Rothbart, & Davis-Stober, 2004).…”
Section: Introductionmentioning
confidence: 99%